Aerodynamic Interference between Oscillating Lifting Surfaces and Fuselage. Part 4: Flapping and Pitching WingsLaws for Micro-Air Vehicles (MAV) in Straight Flight - Valentin Adrian Jean BUTOESCU (INCAS Bulletin, 2014)
In the fourth article of our series we continue to deal with the calculation of the aerodynamic unsteady forces on lifting surfaces. Now we present some applications of the theory discussed in the previous papers to the study of flapping wings.